Ecological significance of standing dead phytomass: Marcescence as a puzzle piece to the nutrient cycle in temperate ecosystems - Mudrák, Ondřej; Angst, Šárka; Angst, Gerrit; Veselá, Hana; Schnablová, Renáta; Herben, Tomáš; Frouz, Jan (The Journal of ecology, 2023)
The plant economics spectrum (PES) drives nutrient cycling through effects on soil decomposers. However, dead phytomass may remain standing or unshed (marcescent), hardly accessible to decomposers and be photodegraded. In arid zones, the significant part of marcescent phytomass can be decomposed without touching the ground. In temperate zones, photodegradation of marcescent phytomass is low but prompts important chemical changes, which affect its subsequent decomposability in the soil and alters the surrounding environment. It is unknown, however, how common marcescence is among different taxa and in which habitats, and how it is coordinated by PES traits. We sampled standing (marcescent) and lying (shed) dead phytomass from a broad spectrum of 127 herbaceous temperate species in a common garden experiment and related these parameters to PES traits, species ecological preferences and phylogeny. Nearly all species (97%) kept their phytomass marcescent. Tall species with a small leaf area and high leaf carbon had a high level of marcescence. Marcescent species also preferred sites affected by severe (but not necessarily frequent) disturbance. The degree of marcescence was considerably conserved in phylogeny. Synthesis. Marcescence extends PES trait effects on ecosystems, particularly in immature habitats, being a common but overlooked phenomenon of the temperate flora. Ekonomické spektrum ekologie rostlin (PES) řídí koloběh živin prostřednictvím složení fytomasy a jejího vlivu na půdní dekompozitory. Odumřelá fytomasa však může zůstat stát nebo neopadat (zůstat marcescentní) a být tak těžko přístupná dekompozitorům ale zároveň vystavena fotodegradaci. V suchých oblastech může být významná část marcescentní fytomasy rozložena fotodegradací, aniž by se dotkla půdy. Naopak v regionech mírného pásma je ztráta marcescentní fytomasy v důsledku fotodegradace nízká. Fotodegradace ale vyvolává důležité chemické změny, které ovlivňují následnou rozložitelnost fytomasy v půdě a mění okolní prostředí. Není však známo, jak běžná je marcescence u různých taxonů a na kterých stanovištích a jak je koordinována s funkčními vlastnostmi PES. V zahradním květináčovém experimentu jsme proto po vegetační sezóně odebrali vzorky stojící (marcescentní) a ležící odumřelé fytomasy ze širokého spektra 127 bylinných druhů mírného pásma. Míru marcescence jsme korelovali s funkčními vlastnostmi, ekologickými preferencemi druhů a fylogenezí. Téměř všechny druhy rostlin (97%) udržovaly alespoň část své fytomasy v marcescentním stavu. Vysoké druhy s malou listovou plochou a vysokým obsahem uhlíku v listech měly vysokou úroveň marcescence. Marcescentní druhy také preferovaly místa postižená silným (ne však nutně častým) narušením. Stupeň marcescence byl ve fylogenezi poměrně silně konzervovaný. Syntéza . Marcescence rozšiřuje vliv PES funkčních vlastností na ekosystémy, zejména na narušených stanovištích, přičemž je běžným, ale přehlíženým jevem flóry mírného pásma.